Self-efficacy, family support, and diet adherence in hypertension at Bestari Health Center - Leony Angelia Sitorus; Venia Rosa Br. Sembiring; Rapael Ginting; Nila Sari (Fakultas Kedokteran, Kedokteran Gigi, dan Ilmu Kesehatan, 2026)
Background: Hypertension is a major public health problem worldwide. Adherence to a low-salt diet is essential for blood pressure control. Self-efficacy and family support are known to influence dietary adherence. This study aimed to analyze the relationship between self-efficacy and family support with low-salt diet adherence among hypertension patients in the working area of Bestari Primary Health Center in 2026. Method: A quantitative descriptive study with a cross-sectional design was conducted. The population comprised 98 hypertension patients registered at Bestari Primary Health Center in December 2023. Total sampling was used, including all 98 patients. Data were collected using validated and reliable questionnaires measuring self-efficacy, family support, and low-salt diet adherence. Data were analyzed using univariate analysis (frequencies and percentages) and bivariate analysis using the Fisher exact test (α = 0.05). Results: Most respondents were male (52.0%), aged 36-45 years (34.7%), had senior high school education (51.0%), and worked as self-employed (48.0%). Low self-efficacy was found in 79.6% of respondents, lack of family support in 59.2%, and non-adherence to low-salt diet in 77.6%. Bivariate analysis showed significant associations between self-efficacy and low-salt diet adherence (p = .014; OR = 4.091, 95% CI [1.413, 11.847]) and between family support and low-salt diet adherence (p = .025; OR = 3.365, 95% CI [1.251, 9.053]). Conclusion: There is a significant relationship between self-efficacy and family support with low-salt diet adherence among hypertension patients in the working area of Bestari Primary Health Center. Patients with low self-efficacy and lack of family support had higher risks of non-adherence. Strengthening patient self-efficacy and family involvement in dietary management is recommended.